THE INFLUENCE OF PERCEPTION OF RESOURCES AND LEARNING INDEPENDENCE ON STUDENT ACHIEVEMENT - Muhammad Yusuf; Syamsu Yusuf (Jurnal Ilmiah Econosains, 2020)
The development of Science and technology requires everyone to be able to use it well for advancement in the era of globalization. Covid-19 Pandemic conditions make students and teachers carry out teaching and learning activities from home. Independence in learning and the perception of learning resources that the teacher is not the only source of knowledge becomes very important in order to improve student achievement. Thus, difficulties in conducting learning activities that are integrate with technology that can be controll. However, on the other hand it remains related to the challenges in increasing student motivation, concentration and independence on learning tasks; In addition, it is also important to provide a way to manage students’ perceptions of technology to be effective and efficient in their knowledge. Therefore, research related to the perception of learning resources and independence becomes an important and difficult problem in improving student achievement so that it can compensate for technological development. This research can discuss the source of learning and independence in learning and its effect on student achievement. With the existence of independent attitudes and perceptions of learning resources within students, learning objectives will succeed in achieving what is expected. This research was conduct at Class XI Private Vocational High School Students in the East Jakarta Region. The population used in this study were all students of class XI with total 450 students. Sampling used by purposive sampling technique. The number of samples obtained was 80 respondents. Based on the results of the analysis, there is significance obtained by students from learning resources and learning independence on the learning achievements of social studies students.